Chemical characterization and antifungal activity of Origanum vulgare, Thymus vulgaris essential oils and carvacrol against Malassezia furfur - Vinciguerra, Vittorio (2018)
The composition of the essential oils (EOs) of O. vulgare L. EO and T. vulgaris EO, were analyzed by GC and GC–MS. Antifungal activities of the EOs and its main component, carvacrol, were evaluated against 27 clinical isolates of Malassezia furfur. Minimum inhibitory concentrations (MICs) were measured according to the broth microdilution protocols by Clinical and Laboratory Standards Institute (CLSI) modified for Malassezia spp. EOs and carvacrol showed low MIC values ranged 450–900 μg/ml against M. furfur. No differences in EOs antifungal activity were observed in sensitive to resistant fluconazole isolates. The antifungal activity obtained showed O. vulgare EO, T. vulgaris EO and carvacrol, their compound, as potential antimicrobial agents against M. furfur, yeast associated with human mycoses.